Methanolic extract of Crotalaria longirostrata: Identification of secondary metabolites and insecticidal effect - López López, Henry (2022)
The complications caused by the generation of resistance in the psyllid Bactericera cockerelli by chemical pesticides, raise the need for the alternative use of products that reduce resistance and ensure better control. The species Crotalaria longirostrata is a source of secondary metabolites, which show possible activity against insect pests. The objective of the research was to identify the compounds of the crude methanolic extract of C. longirostrata leaves, as well as to evaluate their biological activity on B. cockerelli nymphs. Twenty-five compounds were identified by Gas Chromatography coupled to Mass Spectrometry (GC-MS) analysis; the most abundant was 1β,2β-epoxy-1α-methoxymethyl-8α-pyrrolizidine; an alkaloid of the iminosugar group, reported for the first time in C. longirostrata, of which concentrations from 2 to 30 mg/mL of the methanolic extract had to be prepared to evaluate on B. cockerelli nymphs. It showed that at 48 h, there was a mortality of 73.2%-100% in the treatments of 8, 12, 16, 20, and 30 mg/mL. The mean lethal concentration (LC50) was 4.78 mg/mL and LC95 14,52 mg/mL. The results obtained with the methanolic extract of C. longirostrata leaves for controlling the insect B. cockerelli suggest that it can potentially be used as an alternative insecticide of botanical origin to manage the insect.